Any action? Reflections on the Australian Midwifery Action Project. Issue 3 (June 2017) - Gray, Joanne E.; Smith, Rachel M.
Abstract: Background: In 1997 a group of midwifery academics, researchers and practitioners met to discuss issues of concern related to the midwifery profession in Australia. It became clear from this discussion that midwifery in Australia was lagging behind similarly developed countries and that urgent action was required. From this meeting, a plan was developed to seek funding for a major national study into midwifery education and practice standards and as such, the Australian Midwifery Action Project (AMAP) was born. Discussion: This discussion paper presents an overview of a number of midwifery education and regulation changes within the framework of the recommendations from the Australian Midwifery Action Project. A key question arising from this discussion is whether our current midwifery education and regulation standards provide a fit-for-purpose workforce that ensures all women and their families receive best practice midwifery care. Over the past 20 years the Midwifery profession in Australia has undergone significant changes and developments and these changes have had, and continue to have, significant impact on midwifery education and therefore on the quality of midwifery practice in Australia. Conclusion: Many changes have been implemented in the nearly 20 years since AMAP was first conceived. However, many of the issues that provided the impetus for a project such as AMAP remain and are still to be resolved. The midwifery profession continues to be subsumed with nursing, it is not possible to gain accurate midwifery workforce data and, despite the development of national standards for midwifery education, wide variations in courses still exist across Australia.